Respuesta :
Answer:
(-2, -3)
Step-by-step explanation:
We are given y = 3x + 3 and y = x - 1.
We can substitute y = x + 1 into the y value for y = 3x + 3, so
x - 1 = 3x + 3 Now, we just subtract x from both sides.
-1 = 2x + 3 We subtract 3 from both sides.
-4 = 2x
2x = -4 We divide both sides by 2
x = -2 Now we have our x value - (-2, y)
Let's substitute the x value into both of the equations given.
1st equation:
y = 3(-2) + 3
y = -6 + 3
y = -3
2nd equation:
y = (-2) - 1
y = -3
We now know that both equations give us the same y value when x = -2 is substituted, therefore our solution is:
(-2, -3)
The solution for the pair of equations is (-2,-3).
What is a system of equation?
A system of equations is a set or collection of equations that you deal with all together at once. For a system to have a unique solution, the number of equations must equal the number of unknowns.
For the given situation,
The pair of equations are
y = 3x + 3 ------- (1)
y = x − 1 -------- (2)
Substitute the equation 2 in equation 1, we get
⇒ [tex]x-1=3x+3[/tex]
⇒ [tex]3x-x=-1-3[/tex]
⇒ [tex]2x=-4[/tex]
⇒ [tex]x=-2[/tex]
Now substitute x in equation 2,
⇒ [tex]y=-2-1[/tex]
⇒ [tex]y=-3[/tex]
Hence we can conclude that the solution for the pair of equations is (-2,-3).
Learn more about system of equations here
https://brainly.com/question/25818432
#SPJ2